Determinan Financial Distress Pada Perbank Syariah di Indonesia Tahun 2015-2019 - Dhika Restiana; Fajar Satriya Segarawasesa (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aimed to determine the factors that affect financial distress conditions in Islamic commercial banks in Indonesia. The factors include leverage, profitability, liquidity, independent commissioners and audit committees. This research used the quantitative method. The population of this study was Sharia Commercial Bank in Indonesia using purposive sampling methods. The data collection techniques were carried out using secondary data of Islamic bank annual reports in 2015-2019. The results showed that the resulting regression equations of leverage, independent commissioners, and audit committees did not affect financial distress. Meanwhile, profitability and liquidity positively affect financial distress; This research is expected to help related parties minimise financial distress conditions by paying attention to financial ratios such as profitability and liquidity. By paying attention to these aspects, Islamic banks are expected to increase productivity and financial performance in the company to avoid financial distress.